2019
DOI: 10.1007/978-3-030-28005-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Personality Traits in a Large Scale Software Development Company: Exploratory Industrial Case Study

Abstract: Software development methodologies become increasingly more people and team-oriented. However, many software projects fail due to conflicts of team members. Formation of an effective software development team may be particularly challenging given the differences inherent across an individual's personality. This paper explores personality traits of agile software development teams by using a context-specific interactive assessment. Concerning the assessment, we have conducted a questionnaire with 110 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Later, context cards were employed in another study that used the gamification approach to improve the software development process by exploring the personality of software practitioners 16 . Moreover, in an exploratory case study, this approach was used 51 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, context cards were employed in another study that used the gamification approach to improve the software development process by exploring the personality of software practitioners 16 . Moreover, in an exploratory case study, this approach was used 51 …”
Section: Methodsmentioning
confidence: 99%
“…First, the assessment model uses a group of contextual questions based on the situations faced at the software domain, which presents familiar concepts to practitioners and assists to retrieve to attain a more accurate judgment. This assessment was an exclusive example within the software engineering field, and it was published in recognized conferences and journals 18,50,51 . Moreover, this approach was quite straightforward to implement in a large‐scaled software company due to its systematic manner and interactive game concepts.…”
Section: Methodsmentioning
confidence: 99%
“…They found managers to be more conscientious and extroverted, and agile developers to be more neurotic and extroverted. Akarsu et al [4] studied the personality traits by administering the BFI to 18 agile teams. They found that high levels of agreeableness and conscientiousness were common in most teams.…”
Section: Personality Detection In Sotware Engineeringmentioning
confidence: 99%
“…Now, from the pedagogical point of view, it is confirming that not considering criteria related to personality traits before the group formation has generally led to lower results. Taking into account personality traits in the group formation process enhances their collaborative performance when it comes to software development activities [78,[82][83][84][85][86][87][88][89][90]. In this aspect, the highlight of the study is that those groups whose formation has been pre-established by the teachers through the proposed strategy, in general, have had a better collaborative performance than groups with traditional formation, except in the case of heterogeneous training.…”
Section: Conclusion and Further Workmentioning
confidence: 99%